2012
DOI: 10.1080/09718923.2012.11893074
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Personality Traits and Resilience on Burnout among Customer Service Representatives in a Call Centre

Abstract: The aim of the study was to identify those personality traits and resilience factors that could influence the ability of Customer Service Representatives in a call centre to manage burnout effectively. A crosssectional survey design was used and the sample consisted of 187 customer service representatives from a call centre. The Big Five Personality Structure was utilised to measure personality traits by means of the International Personality Item Pool. The Resilience Scale and the Maslach Burnout Inventory (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…The importance of workforce and organisational resilience has been highlighted by Kotze and Lamb (2012), who assert that measures that increase these will help nurse leaders to make sound decisions in critical moments.…”
Section: Resiliencementioning
confidence: 99%
“…The importance of workforce and organisational resilience has been highlighted by Kotze and Lamb (2012), who assert that measures that increase these will help nurse leaders to make sound decisions in critical moments.…”
Section: Resiliencementioning
confidence: 99%
“…Second, resilience is related to adaptive functioning in work environments. For example, Kotze and Lamb () found that resilient employees in a call center relied more on their personal abilities and less on external support in responding to challenges. Carvalho, Calvo, Martin, Campos, and Castillo () demonstrated that resilience is inversely related to emotional exhaustion from work.…”
Section: Resiliencementioning
confidence: 99%
“…There are many definitions of resilience; it is generally described as the ability of an individual to successfully adapt, maintain competent functioning, and ‘bounce-back’ from adversity and major life stressors [ 1 , 6 , 7 ]. Emotional resilience is defined as an individual’s ability to adapt to various adverse conditions while maintaining a sense of purpose, balance and positive mental and physical wellbeing [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Literature suggests that resilient individuals are better equipped to deal with the stressors that result from a constantly changing work environment. They are more likely to make sound decisions in critical moments, and less likely to be off sick or chose to leave the organisation due to organisational stressors saving the organisation money [ 6 ].…”
Section: Introductionmentioning
confidence: 99%